EFEKTIVITAS PENERAPAN PRINSIP KEADILAN DAN EFISIENSI PEMBIAYAAN PENDIDIKAN DI SMP N KABUPATEN KENDAL - Rias Dewi Setyowati; Mudzalifah; Mardiman; Nurkolis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aims of this research are 1) to determine the application of the principles of justice and efficiency in education financing. 2) to determine the effectiveness of the application of the principles of justice and efficiency in financing education for SMP N Kendal Regency. Researchers use mixed methods research, namely a combination of qualitative and quantitative methods. In data collection techniques, researchers used interview techniques with informants, distributing questionnaires and documentation. To analyze quantitative data, multiple regression is used as a data analysis technique with the F test and t test. The results of the research are 1) the school principal designs a budget that is aligned with the needs of the school program. School budget activity plans are made fairly without any discrimination in certain school programs and the budget draft is in line with JUKNIS. Implementation of the principle of efficiency by spending according to needs and on target. 2) Effectiveness of implementing the principles of justice and efficiency in financing education at SMP N Kendal Regency. The results of multiple regression analysis show the equation Y ̂=2.557+0.813X_1+393X_2. The effectiveness of the principles of justice and efficiency in financing Kendal Regency High School education is 76.2%. The author suggests that the education office provide training to school principals so they can better understand the aims and objectives of education financing.